Asset Structure Impact on Capital Structure of Capital Market-Listed Firms in Indonesia and Malaysia - Zainal Abidin Sahabuddin (Jurnal Keuangan dan Perbankan, 2017)
The debt was able to be used by the firm as a source of funds for investment-related activities, especially when the amount of retained earnings was not sufficient to cover the amount of investment needed. Naturally, the use of debt definitely caused the agency conflict between firm shareholders and debt holders. To reduce this conflict, the existence of fixed assets as collateral was needed when the firm decided to borrow money from debt holders. The purpose of this study was to prove the agency theory perspective by testing an impact of asset structure on the capital structure of firms. The population of this study was the firms listed on the Indonesia Stock Exchange and Malaysian Stock Exchange. The firms as a sample were taken from the population by conducting a stratified random sampling method. The pooled data regression model was used as the data analysis method. This result of this study showed that asset structure had a positive impact on the capital structure. It meant the causal relationship between asset structure and capital structure happened and was supported by the agency theory perspective.DOI: https://doi.org/10.26905/jkdp.v21i3.1312